A comparison of three treatment methods for fractures of the mandibular angle. Issue 7 (July 2016) - Kim, M.-Y.; Kim, C.-H.; Han, S.-J.; Lee, J.-H.
Abstract: The purpose of this study was to determine a practical and cost-effective treatment method for fixing mandibular angle fractures using miniplates. Patients were divided into three groups for comparison, based on the intraoperative plates and maxillomandibular fixation (MMF) used: group A, single miniplate fixation with MMF ( n = 37); group B, double miniplate fixation with MMF ( n = 59); group C, double miniplate fixation without MMF ( n = 38). Details of the characteristics of the fractures and the treatments and outcomes were collected retrospectively and analyzed statistically. This study was based on 134 cases of isolated mandibular angle fracture. Of the surgically treated patients, 78.4% ( n = 105) were completely free of complications. A detailed complication correlation matrix is given in the text. Besides screw loosening and malocclusion, no statistically significant difference was observed between the groups. The results of this study suggest that treatment with single miniplate fixation and MMF has a low incidence rate of complications, and this method of treatment is considered to be simple.